ANALISIS PENGARUH INFRASTRUKTUR PADA WISATA ALAM NEGERI DI ATAS AWAN KABUPATEN TORAJA UTARA - Bate Pongsitanan; Harmonis Rante; Tiurlina Siregar (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
One of the most visited natural attractions is tourism with natural scenery in the form of clouds that can be seen in a place that is higher than the clouds. This tour is better known as the Land Above the Clouds, which is precisely located in Lolai Village, Kapalapitu District, North Toraja Regency, South Sulawesi Province. According to the Tana Toraja Regency Culture and Tourism Service (Disbudpar), tourism development in Tana Toraja Regency is still constrained by infrastructure and supporting facilities. Tourism infrastructure is natural and man-made resources that are absolutely needed by tourists traveling in tourist destinations, such as roads, electricity, water, telecommunications, terminals, bridges and so on. In the development of NDA-L tourism infrastructure, the North Toraja district government is more dominant because they can take multiple benefits from this development, such as increasing the flow of information, economic traffic flow, the flow of human mobility between regions and so on which of course can increase business opportunities and work. With the better condition of roads and infrastructure at the NDA-L tourist sites, it is not surprising that there are increasing tourist visits. Especially on holidays or holidays. The number of visitors can be up to 20 thousand visitors per day. Of course this will be very beneficial in terms of the economy and tourism development. Especially for economic improvement through the tourism industry, there are many benefits that can be taken if the existing economic industry can develop optimally.